Sistem Informasi Manajemen Persediaan Barang Berbasis Multiuser - Kasih Purwantini; Sri Wahyuning; Hendri Rasminto (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
During the period of rapid development of technology and information systems encouraging the public, both groups and individuals, both government and private agencies to take advantage of technological developments, technology has a very important role in the progress of human life. Technological developments, one of which is the advantage of computers in processing data, can increase effectiveness, productivity and efficiency in carrying out work, in current technology it makes it easier for work to manage inventory. The Sumber Rejeki Gubug Building Store is located at Jl. Gamblok Market, Ngroto Village, Gubug District, Grobogan Regency, the current inventory and sales system still uses archived paper records. The process of preparing or procuring goods is still carried out manually, namely by checking directly on the remaining goods. Checking goods data and stock data is recorded on a piece of paper by the admin as a report to the leadership